The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/ccd.1810280218
|View full text |Cite
|
Sign up to set email alerts
|

Selective coronary angiography via antegrade venous route in congenital cyanotic heart disease

Abstract: An antegrade venous technique was utilised to perform selective coronary angiography in cyanotic infants and children. The procedure was successful in 88% (37/42) cases and excellent quality angiograms were recorded. The importance of proper catheter selection and details of the technique are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…We believe that the selective angiographic study is necessary, because it allows analysis of left coronary anatomy, flow balance between the left coronary and collateral vessels, and a more correct planning of the surgical approach. The catheterization, using the femoral vein approach, of coronary arteries arising from the aorta in children with congenital heart diseases has been previously described 9 and is a simple procedure, because in children the aorta is small in diameter. But difficulties exist for selective catheterization of the left coronary artery arising from the pulmonary trunk in adults, due to the large trunk diameter and the curve of the catheter at the tricuspid valve.…”
mentioning
confidence: 99%
“…We believe that the selective angiographic study is necessary, because it allows analysis of left coronary anatomy, flow balance between the left coronary and collateral vessels, and a more correct planning of the surgical approach. The catheterization, using the femoral vein approach, of coronary arteries arising from the aorta in children with congenital heart diseases has been previously described 9 and is a simple procedure, because in children the aorta is small in diameter. But difficulties exist for selective catheterization of the left coronary artery arising from the pulmonary trunk in adults, due to the large trunk diameter and the curve of the catheter at the tricuspid valve.…”
mentioning
confidence: 99%
“…Anatomically more important, the right coronary artery ostium is located at a site close to the VSD and anterior in TOF [7,8,10], making the right coronary catheter insertion easier. In cases of complex congenital heart disease (TOF, truncus arteriosus, double outlet right ventricle), a selective coronary arteriography is possible through VSD using a technique similar to that usually applied in the right heart catheterization [6]. In young children, up and down movements of the aortic root occur due to respiration and cardiac systole, but this cyclic deviation is very small and probably causes no technical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…During transvenous coronary arteriography through a VSD, the selective coronary catheters run through the two cardiac valves, such as the tricuspid and the aortic valves, requiring some technical skill compared to the transarterial arteriography, which does not involve the valves. Loya et al [6] preliminaryly reported the selective coronary angiography via the antegrade venous route and showed the need of a newly designed catheter to simplify the procedure. We have independently developed this transvenous procedure and made two preshaped catheters for cases with TOF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations